Layout Optimization of Rail Expansion Joint on Long-Span Cable-Stayed Bridge for High-Speed Railway. (27th July 2020) - Cai, Xiaopei; Liu, Wanli; Xie, Kaize; Zhu, Wenjun; Tan, Xiyuan; Gao, Yongjie
Abstract : Continuous welded rail (CWR) has been widely applied to the Chinese high-speed railways. It is interesting to reduce the effect of rail longitudinal force on the long-span cable-stayed bridges. Taking the pile-soil interaction into account, the finite element model of CWR on the long-span cable-stayed bridge is established based on the bridge-track interaction theory. The rail longitudinal force can be reduced and the track stability can be improved significantly by installing Rail Expansion Joint (REJ). The layout scheme of REJ plays a controlling role on designing CWR on bridges. Results show that the unidirectional REJ should be laid on both ends of the long-span cable-stayed bridge. Switch rails of REJ are set up on the main beam, stock rails are laid on the simply supported beams and crossing over beam joints, and several-meter long small resistance fasteners need to be laid on the sides of stock rails to reduce the fixed pier longitudinal force near the main beam. The range of REJ laid on cable-stayed bridge is mainly determined by temperature, rail breaking, and seismic condition; the bending and braking loads have little influence on it. Multiple field tests are carried out to prove the validity of the numerical model and the design methodology.